Neuroticism and Emotional Intelligence of Polish Teachers - Marta Izabela Sterlus; Ryszarda Ewa Bernacka (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: The implementation of educational tasks by teachers occurs in the context of emotional relationships with students, their parents, the school administration, and other teachers. Neuroticism and emotional intelligence are particularly important given that this is one of the most emotionally exhausting professions. Research Aim: The aim of the study was to explore whether neuroticism is a predictor of teachers' emotional intelligence and whether there is variation in these given seniority and the type of subject taught. Method: The following questionnaires were applied: Eysenck Personality Questionnaire EPQ-R(S); scale the Neuroticism in the NEO-PI-R personality questionnaire; Popular Questionnaire of Emotional Intelligence PKIE. Results: A predictor of high emotional intelligence is low neuroticism (of the Big Three-PEN Eysenck). Low neuroticism among teachers is associated with high emotional intelligence. Teachers with seniority of more than 20 years have significantly lower neuroticism (of the Big Five) including depressive sub-trait and higher emotional intelligence including control over their own emotions. Conclusions: Increasingly proficient emotion management can be predicted with years of service provided, but when the teacher is low in neuroticism. These findings may be important for the diagnosis and professional counseling of teachers and inspire continuous psycho-educational interventions to improve their emotional intelligence.